MODEL MANAJEMEN KELAS BAGI ANAK LAMBAN BELAJAR DI ERA NEW NORMAL - Muhammad Ziaulhaq; Anggih Tri Cahyadi (Idaarah: Jurnal Manajemen Pendidikan, 2022)
The purpose of this study is to find out an overview of the classroom management model for children who are slow learner in the New Normal Era at SDN 13 Kolo. This type of research is descriptive qualitative research with data sources from teachers and homeroom teachers. Data collection techniques are carried out by interviewing, observing and validating data carried out by extending observations, triangulation and member checks, then analyzed by following the concepts of Miles and Huberman. The results showed that there is a class management model for children to be slow learner by creating a learning climate through methods of providing practical activities, applauding enthusiasm to build confidence in children slow learner, providing ice breaking to relieve boredom of children slow to learn, inviting children to be slow learner on the beach, using tab media to strengthen children's learning slow to learn and providing left brain balancing and right brain via YouTube video. The classroom arrangement for children to learn to use the seating model in a circular manner in order to interact with peers, make group discussions with peers. Designing a class model using student drawings, designing a sitting position on the reading floor, good lighting conditions, teacher interaction model to children slow learner using a one-way interaction method by directly approaching the child to be given special services in the context of Bima local culture, namely ‘ngoa ra tei’ (naturing) in the hope that children can foster enthusiasm in learning and can interact with peers.